Conceptualization of Chavez Cross-Cultural Community Extension Theory - Maribel M. Chavez; Marsha H. Malbas; Benjamin D. Tiongzon; Mathea M. Baguia (Journal of Sociological Research, 2024)
This study intends to conceptualize the conglomeration of cultures between the villagers of a Zambian community and the missionary-educators. With the missionary-educators extending their activities in the village for more than a decade, the village people were positively responding. Thus, there was a gradual cultural adaptation. With the constant challenges in basic needs, language -communication between missionary educators and the villagers, cultural differences, and education. The missionary educators strategically intervened the incumbent lives of the villagers in order to update them with the world trends. The activities and effort of the missionary educators were designed formally through projects and programs intervention. The researchers conceptualized the theoretical abstract of the merging cultural practices between villagers and the missionary-educators. Though strategically intentional programmed and created, the missionary learned and the adapted particular cultures of the villagers which maximize their realization about cross-culture.